The Influence of Halal Labeling, Word of Mouth and Perceived Quality on the Decision to Purchase Body Lotion Scarlett Whitening Among Gen Z in Banda Aceh City - Ayuna, Dyla; Sitepu, Novi Indriyani (International Journal of Kita Kreatif, 2025)
This study aims to examine the influence of halal labels, word of mouth and perceived quality on purchasing decisions for Scarlett Whitening body lotion. The sample in this study was generation Z in Banda Aceh City who used Scarlett whitening body lotion products with a total of 100 respondents taken based on the Slovin technique. The data used in this research is primary data. The analysis used in this research is multiple linear regression analysis. The results of the research show that partially the halal label variables, word of mouth and perceived quality have a significant positive effect on the decision to purchase Scarlett Whitening body lotion. Then simultaneously the halal label variables, word of mouth and perceived quality have a significant positive effect on the decision to purchase Scarlett Whitening body lotion. The findings of this research provide insight to consumers and producers to ensure that there is a halal label on product packaging and consider the word of mouth aspect or word of mouth recommendations by improving product quality to provide a satisfying experience for consumers.